THE RELATIONSHIP BETWEEN INTENSITY OF WORSHIP AND THE STRENGTHENING OF FAITH IN CHILDREN ; THE ISLAMIC RELIGIOUS EDUCATION BASED ON THE 7 HABITS OF GREAT INDONESIAN CHILDREN PERSPECTIVE - Nur Alfiyani; Muhammad Kafal Faza (MISBAH : Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze the relationship between worship intensity and faith strengthening in children from the perspective of Islamic Religious Education (PAI) and the 7 Habits of Great Indonesian Children program. Using a library research method with a qualitative approach, this study examines relevant literature through stages of data reduction, data presentation, interpretation, and conclusion drawing. The results show that worship intensity has a close relationship with children's faith strengthening through four main mechanisms: (1) internalization of faith values through consistent worship habituation, (2) building emotional and spiritual closeness with Allah SWT, (3) forming positive habits that become children's character, and (4) developing intrinsic motivation in religion. The implementation of worship habits in the 7 Habits of Great Indonesian Children program is carried out through a holistic approach involving family, school, and community by integrating the values of tawhid, worship, morality, and muamalah. Challenges faced include the influence of digital technology, lack of role models, less engaging educational approaches, and socio-cultural pressures. Solutions include wise technology management, increased role modeling, development of creative learning methods, and building children's spiritual resilience. This research provides theoretical contributions to the development of PAI and practical recommendations for educators and parents in strengthening children's faith through systematic and sustainable worship habituation. Keywords: worship intensity, faith strengthening, Islamic Religious Education.